2023
DOI: 10.3390/cancers15112927
|View full text |Cite
|
Sign up to set email alerts
|

Early Prediction of Response Focused on Tumor Markers in Atezolizumab plus Bevacizumab Therapy for Hepatocellular Carcinoma

Abstract: Despite the promising efficacy of atezolizumab plus bevacizumab (atezo/bev), some patients with unresectable hepatocellular carcinoma (HCC) experience disease progression. This retrospective study, which included 154 patients, aimed to evaluate predictors of treatment efficacy of atezo/bev for unresectable HCC. Factors associated with treatment response were examined, focusing on tumor markers. In the high-alpha-fetoprotein (AFP) group (baseline AFP ≥ 20 ng/mL), a decrease in AFP level > 30% was an independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…However, it has been reported that patients who achieved DCR during Dur/Tre treatment had longer median survival ( 20 ). Thus, achieving DCR during immunotherapy is important for longer survival ( 21 ). Although there was no significant difference in PFS between the first-line and later-line therapies in this study, this result may change if the observation period is extended.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that patients who achieved DCR during Dur/Tre treatment had longer median survival ( 20 ). Thus, achieving DCR during immunotherapy is important for longer survival ( 21 ). Although there was no significant difference in PFS between the first-line and later-line therapies in this study, this result may change if the observation period is extended.…”
Section: Discussionmentioning
confidence: 99%
“…However, AFP has limited value, as only a minority of patients have increased levels (10% of patients at early stages have AFP >400 ng/dL scaling up to 40% in advanced stages) [ 10 , 11 ]. On the other hand, early changes in AFP may predict the benefit of systemic agents like Ramucirumab [ 9 ] or the combination of Atezolizumab plus Bevacizumab [ 12 ].…”
Section: Introductionmentioning
confidence: 99%